2012
DOI: 10.1007/s00436-012-3068-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Giardia duodenalis in children from the Cufada Lagoon Natural Park, Guinea-Bissau

Abstract: Molecular characterization of Giardia duodenalis in African countries is relatively scarce. The global understanding of Giardia epidemiology is reinforced when more data are available from highly endemic countries. In the present study, 50 fecal samples collected from children from Guinea-Bissau were screened for Giardia infection. Amplification of the Giardia ssu-rRNA fragment was achieved for 28 samples (28/50, 56.0 %) of which 23 (23/50, 46.0 %) positive samples for Giardia were detected through microscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
1
10
1
1
Order By: Relevance
“…In no case were highlighted animal-specific assemblages (from C to G). The existing data on human genotypes characterized in African countries are still limited and fragmented, covering Egypt [15,16], Ethiopia [17], Western Sahara [18], Guinea Bissau [19] and Cote d'Ivoire [7]. The distribution of assemblages observed among our samples does not differ considerably from those observed in other African countries where a higher rate for assemblage B is already known, e.g.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 63%
“…In no case were highlighted animal-specific assemblages (from C to G). The existing data on human genotypes characterized in African countries are still limited and fragmented, covering Egypt [15,16], Ethiopia [17], Western Sahara [18], Guinea Bissau [19] and Cote d'Ivoire [7]. The distribution of assemblages observed among our samples does not differ considerably from those observed in other African countries where a higher rate for assemblage B is already known, e.g.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 63%
“…Kohli et al (2008) [13], in North-eastern Brazil, reported that children infected with assemblage B eliminate larger numbers of cysts compared to those infected with assemblage A. A higher frequency of assemblage B has also been observed by other authors [29,33,34]. In contrast, Volotão et al (2007) [10], Souza et al (2007) [35] in Brazil and Zhang et al (2012) [36] in China found a predominance of genotype A, when specimens from humans and dogs were analysed.…”
Section: Discussionmentioning
confidence: 84%
“…DNA was extracted from all samples in which Entamoeba histolytica/dispar cysts were detected by microscopy [ 12 13 ]. Molecular identification of E .…”
Section: Methodsmentioning
confidence: 99%